Potential Pathogens Associated with Colorectal Cancer - Nezhadi, Javad; Kafil, Hossein Samadi; Mahdavi, Farshad; Sadrkabir, Mohammad; Hashemzadeh, Shahryar; Moaddab, Seyed Yaghoub; Nouri, Roghayeh; Mohammadzadeh-Asl, Yalda; Sattarpour, Simin; Rezaee, Mohammad Ahangarzadeh (Current Pharmaceutical Biotechnology, 2025)
Colorectal Cancer (CRC) is a malignancy in which the cells of the colon and rectum grow uncontrollably. This disease initially appears as an adenomatous polyp, which, over time, turns into an advanced adenoma with high-grade dysplasia and becomes the basis of invasive cancer. Dysbiosis refers to the reduction of microbial diversity and disruption of the balance in the population of beneficial (microbiota) and harmful (pathogenic) microorganisms. The disruption of the balance causes an increase in pathogenic microbial species, which play a role in creating a pro-inflammatory environment. Therefore, dysbiosis can disrupt the balance of the microbiota population, leading to Gastrointestinal (GI) disorders like cancer. According to research, it has been established that certain pathogenic bacteria, specifically Fusobacterium nucleatum, Escherichia coli, Bacteroides fragilis, Enterococcus faecalis, Streptococcus gallolyticus Helicobacter pylori, Salmonella enterica, Campylobacter jejuni, and Peptostreptococcus anaerobius are capable of thriving in a state of dysbiosis and can significantly contribute to the progression of CRC. This study aims to discover the role and various mechanisms of the mentioned pathogenic bacteria in the development and progression of CRC and their effect on cellular and immune changes. The findings of this research could highlight the importance of diagnosis and treatment of these microorganisms in the context of CRC and lay the groundwork for future research in this field.
Keywords: pro-inflammatory environment